2015
DOI: 10.1021/acs.joc.5b01906
|View full text |Cite
|
Sign up to set email alerts
|

β-Functionalized Push–Pull opp-Dibenzoporphyrins

Abstract: The synthesis of a series of β-functionalized push-pull dibenzoporphyrins was realized. These porphyrins display subtle push-pull effects, demonstrating the exceptional tunability of their electronic and electrochemical properties. The UV-vis spectra of these porphyrins show unique absorption patterns with shouldered Soret bands and extra absorptions in the Q-band region. Stronger electron-withdrawing groups display more significant bathochromic shifts of the Soret bands. The fluorescence spectra of these porp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Cresyl violet perchlorate (0.55 in methanol) and methylene blue (0.03 in methanol) were used as external standards for BODIPYs 2 , 6a , 6b , 4 and 3 , 7 , 8 , respectively. The relative fluorescence quantum yields (Φ f ) were determined using the following equation (1), 4c ϕx=ϕR[GradXGradR][ηX2ηR2]where Φ represent the fluorescence quantum yields; ƞ represent the refractive indexes of solvents; Grad represent the gradient from the plot of integrated fluorescence intensity vs absorbance at λ ex ; Subscripts X and R represent the tested sample and standard sample respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Cresyl violet perchlorate (0.55 in methanol) and methylene blue (0.03 in methanol) were used as external standards for BODIPYs 2 , 6a , 6b , 4 and 3 , 7 , 8 , respectively. The relative fluorescence quantum yields (Φ f ) were determined using the following equation (1), 4c ϕx=ϕR[GradXGradR][ηX2ηR2]where Φ represent the fluorescence quantum yields; ƞ represent the refractive indexes of solvents; Grad represent the gradient from the plot of integrated fluorescence intensity vs absorbance at λ ex ; Subscripts X and R represent the tested sample and standard sample respectively.…”
Section: Methodsmentioning
confidence: 99%
“…[ 23 ] For the synthesis of TATBP 5 , 4,7‐dihydro‐5,6‐dimethoxycarbonyl‐4,7‐ethano‐2 H ‐isoindole 2 , which was prepared by a modified literature procedure [ 24 ] (see Supporting Information) was utilized for the acid‐catalyzed condensation with 4‐ tert ‐butylbenzaldehyde yielding the desired TATBP 5 in 49 %. Jinadasa et al [ 25 ] demonstrated the post‐functionalization of such ester substituted porphyrins with anilines to the corresponding N ‐phenyl‐phthalimido derivatives. Hence, the reported reaction conditions were modified for the condensation of the two building blocks 5 and HAB‐NH 2 to the corresponding tetrakis‐ N ‐HAB‐phthalimido‐porphyrin 6 , which was obtained in 64 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…Dibromobenzoporphyrins 3a and 3b were obtained throughr egioselective bromination of 2a and 2b by using N-bromosuccinimide( NBS)i nd ry CHCl 3 . [15] Pushpull opp-dibenzoporphyrins 4a and 4b were generated from methyl acrylate and 3a and 3b,r espectively, by using aH eckbased cascade reactioni nt he presence of aP d 0 catalyst formed in situ. We also tried the Pt[P(tBu) 3 ] 2 /Pd 2 (dba) 3 catalyst system for this reaction; however,itd id not lead to the desired product.…”
Section: Molecular Design and Synthesismentioning
confidence: 99%